2018
DOI: 10.1371/journal.pone.0196686
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasonic nanobubble-mediated PNP/fludarabine suicide gene system: A new approach for the treatment of hepatocellular carcinoma

Abstract: ObjectiveThe purpose of this study is to generate an ultrasonic nanobubble (NB)-mediated purine nucleoside phosphorylase (PNP)/fludarabine suicide gene system for the treatment of human hepatocellular carcinoma (HCC).MethodsNBs were prepared from a mixture the phospholipids 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and 1,2-dipalmitoyl-sn-glycero-3-phosphate (DPPA), perfluoropropane gas and other materials using the high shear dispersion method. NBs treated with ultrasound irradiation functioned as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Relatively low-frequency US was irradiation to induce release of siRNA micelles in tumor tissue from the siRNA loaded NBs and then effectively delivered into cancer cells. Furthermore, several promising data have been reported on liver gene therapy by combining various types of NBs and US (Wu et al, 2016;Zhang et al, 2018). Nevertheless, our animal sonoporation study also revealed induction of gene transfer in the liver after intravenous injection of lipid-based NBs.…”
Section: Discussionmentioning
confidence: 61%
“…Relatively low-frequency US was irradiation to induce release of siRNA micelles in tumor tissue from the siRNA loaded NBs and then effectively delivered into cancer cells. Furthermore, several promising data have been reported on liver gene therapy by combining various types of NBs and US (Wu et al, 2016;Zhang et al, 2018). Nevertheless, our animal sonoporation study also revealed induction of gene transfer in the liver after intravenous injection of lipid-based NBs.…”
Section: Discussionmentioning
confidence: 61%
“…In terms of CACYBP , it has been verified that CACYBP can promote hepatocellular carcinoma progression in the absence of RNF41 -mediated degradation [ 22 ]. Moreover, a study [ 23 ] found that PNP /fludarabine suicide gene system induced HCC cell apoptosis and inhibited the growth of HCC cells. Although we found no evidence supporting the correlation between SKAP2 and HCC, it has been verified that SKAP2 promotes podosome formation to facilitate tumor-associated macrophage infiltration and metastatic progression [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of CACYBP, it have been verified that CACYBP can promote hepatocellular carcinoma progression in the absence of RNF41 mediated degradation [22]. Moreover, a study [23] found that PNP/fludarabine suicide gene system induced HCC cell apoptosis and inhibited the growth of HCC cells. Although we found no evidence supporting the correlation between SKAP2 and HCC, it has been verified that SKAP2 promotes podosome formation to facilitates tumor-associated macrophage infiltration and metastatic progression [24].…”
Section: Discussionmentioning
confidence: 97%